An urgent call for using real human urine in decentralized sanitation research and advancing protocols for preparing synthetic urine - Simha, Prithvi; Courtney, Caitlin; Randall, Dyllon Garth (Frontiers in Environmental Science, 2024)
Recycling resources excreted in human urine can help achieve a sustainable future and circular economy in the sanitation space. However, many studies researching different technologies for safely recycling urine do not use real human urine for experimentation, relying instead on recipes for making synthetic or artificial solutions that attempt to mimic the composition of real human urine. This methodological choice is the focus of this article, which points out that the real urine matrix is extremely complex, with a metabolome (>2,500 metabolites) that differs greatly from that of synthetic urine (<15 metabolites). Therefore, experimental results obtained using synthetic urine can also differ from those obtained using real urine. To exemplify this, we review published literature in terms of four aspects: i) solubility of chemicals and buffering capacity of urine, ii) dissolved organics and membrane fouling, iii) thermodynamic modelling of chemical speciation in urine, and iv) removal of pollutants from urine. We recognise that there is a place for synthetic urine in sanitation research and provide examples of studies where its use is appropriate. Lastly, based on literature from the medical sciences, we provide preliminary guidelines on protocols for preparing synthetic urine that could improve experimentation involving human urine and accelerate the water sector’s transition to circularity.